Droplet-based methods for tackling antimicrobial resistance. (August 2022) - Ruszczak, Artur; Bartkova, Simona; Zapotoczna, Marta; Scheler, Ott; Garstecki, Piotr
Abstract : Application of droplet-based methods enables (i) faster detection, (ii) increased sensitivity, (iii) characterization of the level of heterogeneity in response to antibiotics by bacterial populations, and (iv) expanded screening of the effectiveness of antibiotic combinations. Hereby, we discuss the key steps and parameters of droplet-based experiments to investigate antimicrobial resistance. We also review recent findings accomplished with these methods and highlight their advantages and capacity to yield new insights into the problem of antimicrobial resistance. Graphical Abstract: ga1 Highlights: Droplet-based microfluidics enables faster determination of antimicrobial resistance. Culturing single bacterial cells in droplets enables studies on bacterial consortia by increasing the taxonomic richness of polymicrobial samples. Droplet microfluidics allows for high-throughput verification of bacterial response to combinations of multiple antimicrobials.